2014
DOI: 10.4314/jab.v72i1.99665
|View full text |Cite
|
Sign up to set email alerts
|

Production et retombées minérales des litières chez quatre espèces de légumineuses arborées, utilisées en amélioration de jachères, en zone forestière de Côte d’Ivoire

Abstract: Production et retombées minerals des litières chez de légumineuses arborées, utilisées en amélioration de jachères

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
(1 reference statement)
1
6
0
3
Order By: Relevance
“…Wakwa site had an intermediate position. These results were consistent with those of Gnahoua et al [58], Zhang et al [59] and Diallo et al [60], who showed that the largest amount of litter production was done in the dry season when humidity is low and was low during the rainy season when the humidity was high.…”
Section: Effects Of Soil Types On Litter Productionsupporting
confidence: 93%
“…Wakwa site had an intermediate position. These results were consistent with those of Gnahoua et al [58], Zhang et al [59] and Diallo et al [60], who showed that the largest amount of litter production was done in the dry season when humidity is low and was low during the rainy season when the humidity was high.…”
Section: Effects Of Soil Types On Litter Productionsupporting
confidence: 93%
“…This accumulation of litterfall is much greater than in forests of temperate zones (Andivia et al, 2016) and close to the amount existing in tropical forests (Cassart et al, 2017), and was a consequence of the high productivity of this crop. The nutrients contained in the litter represent a reservoir that will slowly be incorporated into the soil (Sandhu et al, 1990;Parrotta, 1999;Gnahoua et al, 2013) which, together with the contributions from the fine roots (Jha and Prasad Mohapatra, 2010), will maintain productivity of the site. The mineral soil layer showed higher levels of organic matter, water-soluble organic C, N and dehydrogenase activity after 11 years of a Leucaena biomass production system, when compared with the conditions prior to establishing the system, and when compared to adjacent uncropped areas (Table 6), being representative of an increase in soil fertility due to cultivation (Mrema et al, 1997;Peng et al, 2013;Conrad et al, 2017).…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Les légumineuses arborescentes sont dotées de rythmes de croissance très rapides (Dommergues et al, 1999 ;Singh et al, 2004). Elles ont un fort potentiel de production de litière (Bernhard-Reversat et al, 1993 ;Gnahoua et al, 2013) et de bois (Dupuy et Nguessan, 1990). Sein et Mitlöhner (2011) Production de bois par les jachères : Les productions de bois d'Acacia mangium (138 t.ha -1 ) et d'A.auriculiformis (134 t.ha -1 ) ont été les plus importantes tandis qu'Albizia lebbeck (68 t.ha -1 ) a affiché les plus petites quantités.…”
Section: Introductionunclassified